Book Review: An Islamic Perspective on Governance - Maliha, Hasna (SMART Insight, 2025)
Governance has become a central concept in contemporary discourse regarding economic development, political stability, and social welfare. This concept encompasses various dimensions, ranging from corporate governance and economic governance to public governance, which involves mechanisms where political and administrative authorities are used to manage a country's resources. This article presents a synthesis of the book An Islamic Perspective on Governance written by Zafar Iqbal and Mervyn K. Lewis. This book fills a gap in the literature by presenting a systematic analysis of governance issues from an Islamic economic perspective, a viewpoint often overlooked in Western discourse. The authors explore classical and contemporary Islamic sources to build a governance framework, which is then compared with Western perspectives. The focus of the study includes theories of justice, taxation, budget deficits, accountability, and corruption. This article aims to provide a comprehensive understanding of how Islamic principles can be applied in modern governance, while simultaneously offering a critique of conventional approaches.